The Effect of Transformational Leadership, Internship Experience, and Intrinsic Motivation on Work Readiness with Self-Efficacy as a Mediation Variable - Alkusani Alkusani; Sukaris Sukaris; Indro Kirono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Increasing competition in the labor market requires university graduates to demonstrate strong work readiness supported by adaptive skills and self-confidence. This study examines the effects of lecturers’ transformational leadership, internship experience, and intrinsic motivation on students’ work readiness, with self-efficacy as a mediating variable. A quantitative survey was conducted involving 55 Management students who had completed an internship program. Data were collected using a structured questionnaire and analyzed with Partial Least Squares–Structural Equation Modeling. The findings show that lecturers’ transformational leadership, internship experience, and intrinsic motivation do not directly affect work readiness. However, internship experience and intrinsic motivation have a positive and significant effect on self-efficacy, while transformational leadership does not. Self-efficacy significantly influences work readiness and mediates the effects of internship experience and intrinsic motivation. These results highlight the central role of self-efficacy in translating learning experiences and motivation into work readiness. This study is limited by its small sample size and single-institution context, suggesting the need for broader future research.